Heartbreak From Gilteritinib: Two Case Reports of Delayed Onset Cardiotoxicity - Kristi Dutta; Ethan D. Kotloff; Manu M. Mysore (Case Reports in Cardiology)
Activating mutations of FMS-like Tyrosine Kinase 3 (FLT3) occur in a subset of patients with acute myeloid leukemia (AML) and confer a poor prognosis. Gilteritinib, an oral FLT3 inhibitor approved for the treatment of relapsed or refractory AML, has been shown to improve survival and remission rates compared with salvage chemotherapy. This case report presents two patients initiated on gilteritinib for relapsed AML who developed new onset left ventricular systolic dysfunction. After ruling out other common etiologies, gilteritinib was discontinued due to concern for cancer therapy–related cardiac dysfunction with subsequent improvement in ejection fraction. These cases demonstrate a rare but serious adverse effect of gilteritinib, cardiotoxicity manifested as left ventricular systolic dysfunction, for which more studies are needed to elucidate the underlying pathophysiology.